2016
DOI: 10.1016/j.nlm.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of altered associability information by amygdala central nucleus

Abstract: The surprising omission of a reinforcer can enhance the associability of the stimuli that were present when the reward prediction error was induced, so that they more readily enter into new associations in the future. Previous research from this laboratory identified brain circuit elements critical to the enhancement of stimulus associability by the omission of an expected event and to the subsequent expression of that altered associability in more rapid learning. These elements include the amygdala, the midbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 128 publications
(160 reference statements)
1
3
0
Order By: Relevance
“…Eliminating such neurons would thus grant the latter association the upper hand in behavioural control. On the other hand, the deleted ensemble might be critical for restoring attention to the cue in the face of unexpected reward omission and increasing the rate of extinction learning elsewhere (10,31). Although our data are not able to dissociate between these possibilities, both accounts predict that the behavioural scales should be persistently tilted in favour of acquisition, consistent with our findings.…”
Section: Discussionsupporting
confidence: 84%
“…Eliminating such neurons would thus grant the latter association the upper hand in behavioural control. On the other hand, the deleted ensemble might be critical for restoring attention to the cue in the face of unexpected reward omission and increasing the rate of extinction learning elsewhere (10,31). Although our data are not able to dissociate between these possibilities, both accounts predict that the behavioural scales should be persistently tilted in favour of acquisition, consistent with our findings.…”
Section: Discussionsupporting
confidence: 84%
“…Although associative learning happens primarily in the BLA (particularly the lateral nucleus), 40 the CeA is more involved in the generation and processing of prediction error signals. 41,42 Impairment of the CeA may thus contribute to OCD symptoms by reducing the flexibility of behavioural response preferences as a result of a reduction in signalling prediction errors when behavioural choices or preferences are not optimal. Outcome prediction error signalling is crucial for responding to the omission of expected rewards or the occurrence of unexpected punishments, and these are important for modifying learned behaviour to adjust to dynamically changing environments: the hallmark of flexible, adaptive goal-directed behaviour.…”
Section: Cea Impairment May Be Associated With Behavioural Inflexibility In Ocdmentioning
confidence: 99%
“…Another set of studies (Schiffino, 2015; Schiffino & Holland, 2016a) showed that the consolidation of a surprise-enhanced associability memory in the SPT depends on CeA processing 1-4 hours after surprise sessions. Post-surprise infusions of anisomycin, lidocaine, or muscimol prevented subsequent display of surprise-enhanced associability.…”
Section: Memory For Altered Associabilitymentioning
confidence: 99%